Comparison of Hand Grip Strength Among Chefs and Non-Chefs - Mazhar, Fatima; Amjad, Fareeha; Ahmad, Ashfaq (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the handgrip strength among chefs and non–chefs.Study Design: Comparative cross-sectional study.Place and Duration of Study: Different restaurants and hotels of Lahore, from Apr to Sep 2018.Methodology: Thirty-one chefs and 31 non-chefs (waiters and managers) were included in the study. We used a standard method for measuring the handgrip strength of the dominant and non-dominant hand. Handgrip strength was measured with the help of an electronic hand dynamometer (Model EH101).Results: The mean handgrip strength of the dominant hand of the chefs was 39.90 ± 8.50 kg, with the range 22.76 kg-55.30 kg, whereas among non-chefs, the mean handgrip strength of the dominant hand was 38.54 ± 7.85 kg, with the range 21.06 kg52.86 kg. The mean handgrip strength of the non-dominant hand of the chefs was 38.36 ± 7.97 kg, with the range 24.20 kg-56.66kg, whereas, among non-chefs, the mean handgrip strength of non-dominant hand was 37.15 ± 7.26 kg, with the range 23.03kg-51.60 kg.Conclusion: Handgrip strength of chefs and non-chefs was the same in the dominant and non-dominant hands. There was no significant statistical difference in the handgrip strength among chefs and non-chefs.